Determination of Trace Elements in Corydalis conspersa and Corydalis linarioides by ICP-AES - Qing Du; Yanguo Cai; Zhi Chen; Dongliang Wei; Yande Cao; Ying Chen; Shulin Yu; Qianqian Zhao; Jiang Wu; Mingdi Liu (Journal of Chemistry)
In order to establish a method for the simultaneous determination of trace elements Al, As, B, Ca, Cr, Cu, Fe, K, Li, Mg, Mn, Na, Ni, P, Si, Ti, and Zn in Corydalis conspersa and Corydalis linarioides, we collected the samples from different areas and treated with acid hydrolysis into tissues to be detected by the way of inductively coupled plasma-atomic emission spectrometry compared with the standard element control method. We can know that the contents of Al, Ca, Fe, K, Mg, Na, and P in roots, stems, leaves, and flowers were higher. The contents of elements in different tissues and areas were as follows: flower > leaf > stem > root, Zeku County > Guide County > Nangqian County > Henan County. Among them, the contents of each element in the flowers of Maixiu Forest Farm were higher, while the contents of B, Cr, Cu, Li, Mn, Ni, Si, Ti, and Zn in roots, stems, and leaves of other areas were lower. The contents of heavy metal elements complied with the limit degree. A 3-factor model was obtained by principal component analysis which could clarify 82.46% of the total experimental data; the factors of Al, Fe, Mg, Na, P, Ca, Cu, Si, and Zn had great influence on the efficacy of 21 kinds of medicinal materials. Cluster analysis classified the samples into three categories; the flowers of Corydalis conspersa and stems of Corydalis linarioides from different collection areas are clustered containing high contents of type 1 and 3 characteristic components; the roots, stems, and leaves from other collection areas are clustered with low contents of 1 and 2 characteristic components. It can be used for the determination of trace elements in Corydalis conspersa and Corydalis linarioides to provide effective basis for revealing the function of trace elements with plant growth.